Trans-Posterior Cruciate Ligament All-Inside Root Repair Versus Partial Meniscectomy for Medial Meniscus Posterior Root Tears: Comparison of Semiquantitative and Quantitative MRI Outcomes in Cartilage Degeneration and Osteoarthritic Progression. (July 2022) - Su, Jiarong; Wan, Hongyan; Pang, Yingchang; Lu, Yanli; Liang, Jiaming; Yan, Zhigang; Xu, Sibo; Sun, Tiezheng
Objective: To perform conventional, morphological, and T2 mapping compositional MRI imaging to assess the cartilage degeneration and osteoarthritic progression in patients with medial meniscus posterior root tears (MMPRTs) who underwent trans-posterior cruciate ligament (PCL) all-inside repair or partial meniscectomy. Design: Patients with MMPRTs after trans-PCL all-inside repair (group AR) or partial meniscectomy (group PM) between 2015 and 2018 were retrospectively identified. Preoperative and postoperative conventional MRI were collected to assess medial meniscus extrusion (MME) and the whole-organ magnetic resonance imaging score (WORMS). Postoperative morphological MRI and T2 mapping compositional MRI were collected to evaluate the quantitative cartilage thickness/volume and cartilage composition. Results: The final cohort consisted of 21 patients in group AR and 22 patients in group PM, with no differences in demographic data and baseline patient characteristics between the 2 groups. Group AR demonstrated less progression of articular cartilage wear ( P < 0.05) and decreased meniscal extrusion ( P = 0.008) than group PM at the final follow-up. In addition, group AR demonstrated less extracellular matrix degeneration in the cartilage subregion of the medial compartment ( P < 0.05) than group PM with lower T2 relaxation times in the superficial layer of the articular cartilage. Conclusion: Trans-PCL all-inside repair of MMPRTs could delay the initial cartilage deterioration and morphological cartilage degeneration compared with partial meniscectomy. However, the amount of residual meniscal extrusion is clinically important, and an improved root repair fixation method should be investigated.